Diorama of the Directive Constitutional: Reconstruction of Directive Constitutionalism and the Deliberative Crisis in Indonesia’s Constitutional Democracy - Resa Hasan; Luna Dezeana Ticoalu; Averos Aulia Ananta Nur (Staatsrecht: Jurnal Hukum Kenegaraan dan Politik Islam, 2025)
Following the amendments to the 1945 Constitution, Indonesia’s constitutional paradigm has shifted from directive constitutionalism, which emphasizes value-oriented governance, to instrumental constitutionalism, which focuses merely on procedural mechanisms. The abolition of the Broad Outlines of State Policy (GBHN) created a normative vacuum that disrupted the coherence between Pancasila’s constitutional values and national development policies. This condition has led to a deliberative crisis, where public participation in policymaking remains formalistic rather than substantively influential. Using a normative juridical approach and hermeneutic analysis, this study finds that the national development planning system under Law No. 25 of 2004 lacks a strong constitutional foundation to ensure sustainable and value-driven policy direction. Therefore, a reconstruction of directive constitutionalism is required through the establishment of the Guidelines of State Policy (Pokok-Pokok Haluan Negara/PPHN) as a deliberative and participatory constitutional instrument. The Constitutional Court should act as the guardian of constitutional substance through substantive constitutional review, while the People’s Consultative Assembly (MPR) functions as the normative policymaker aligned with constitutional values. This framework aims to reintegrate the constitution, state institutions, and public participation to restore constitutional legitimacy and ensure sustainable, justice-oriented national development.